Meningkatkan Hasil Belajar dan Bernalar Kritis dalam Pendidikan Agama Katolik pada Materi Manusia Sebagai Citra Allah dengan Metode Problem Based Learning Pada Peserta Didik di Kelas VII SMP Negeri 3 Sibolga - Edyolensina Sihotang; Yusmanto Yusmanto; Busri Busri (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Learning in Indonesia aims to increase the intelligence of students intellectually and emotionally. The study of Catholicism, as part of ethics, aims to develop human understanding as a unique image of God. Humans have different uniqueness and abilities, which must be developed through various efforts to benefit themselves, their families, and society. This research aims to improve the learning outcomes of grade VII students of SMPN 3 Sibolga on the material